ANALISIS PERBANDINGAN KINERJA KARYAWAN DI PT. PERUSAHAAN LISTRIK NEGARA (PLN) (PERSERO) WILAYAH NUSA TENGGARA BARAT (STUDI KASUS PADA RAYON AMPENAN DAN RAYON CAKRANEGARA) - Marlina Fujiana Lestari; Zainal Abidin; Rusminah Rusminah (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2019)
The research aim is to find out is there any differences which significant between rayon employees performance at ampenan and rayon employees at cakranegara , this is quantitative comparative research data collecting technique done by interview and documentation population in this research are all rayon employess at ampenan and cakranegara, with the number are 40 person, which consist of 20 of person in rayon ampenan and the same number in rayon cakra yet, the number of population is less than 100 person thus, all employees are made as samples. Analysis data conducted trough t test, and Research result shows that there is no significant different between rayon employees performance at ampenan and rayon employees at cakra in which the significant value is 0.554 or p>0.05, the average value on rayon ampenan is 109.7 and rayon cakra is 108.9, the employees performance have the same ability which more than expectation and extraordinary achievement and they expert in their job thus their performance received should be keeping up trough an exercise to create their quality and technical ability